2019
DOI: 10.1103/physrevx.9.031032
|View full text |Cite
|
Sign up to set email alerts
|

Real-Space Mapping of the Two-Dimensional Phase Diagrams in Attractive Colloidal Systems

Abstract: Phase diagrams reflect the possible kinetic routes and guide various applications such as the designed assembly and synthesis of functional materials. Two-dimensional (2D) materials have been a focus of ongoing research due to their wide applications; therefore, researchers are highly motivated to discover the general principles that control the assembly of such materials. In this study, we map the 2D phase diagrams of short-and long-range attractive colloids at single-particle resolution by video microscopy. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
17
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 64 publications
3
17
1
Order By: Relevance
“…Analysis of the case m = 9 (LJ12-9), very close to that studied in Ref. 65 , demonstrated that for short-range attraction in complex solvents we should witness the third melting scenario.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…Analysis of the case m = 9 (LJ12-9), very close to that studied in Ref. 65 , demonstrated that for short-range attraction in complex solvents we should witness the third melting scenario.…”
Section: Discussionsupporting
confidence: 67%
“…The role of attraction can be tested experimentally in colloidal systems, known for a long time as model systems demonstrating a wide range of "molecularlike" phenomena 1,[47][48][49][50] , in particular, crystallization and melting [51][52][53][54][55][56][57][58][59] , solid-solid phase transitions [60][61][62] , condensation and critical phenomena [63][64][65] caused by relatively short-range attractive depletion forces 66 . These collective phenomena can be visualized in real-time with spatial resolution of individual particles.…”
Section: Introductionmentioning
confidence: 99%
“…Several authors have used this parameter to quantify the two-dimensional crystallisation process 45 47 . It also allows us to identify phase transitions—for instance, from a liquid to a crystalline lattice 48 , 49 .…”
Section: Methodsmentioning
confidence: 99%
“…Much research has been devoted to three-dimensional (3D) self-assembly [25], though a two-dimensional (2D) variant continues to be of interest from an exploratory perspective [47][48][49][50][51][52][53][54][55] as well as in applied technologies [1,56]. Optimal function is achieved via slab geometry in many devices, including optoelectronic/photonic materials [57][58][59][60][61], sensors [60,[62][63][64][65][66][67][68], display technologies [69][70][71], smart glass [72,73], spatial light modulators [74][75][76][77], and tunable filters [78][79][80][81].…”
Section: Introductionmentioning
confidence: 99%